The Rate of Blood Glucose Utilization in Thin Tailed Weaner Lambs Following a 5-week Feed Restriction - Yuwono, P; Sodiq, A (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2006)
The purposes of the experiment were to investigate the effect of feed restriction on the rate of whole body glucose utilization and to examine relationship between basal glucose concentration in the blood and the rate of whole body glucose utilization. A total of 12 thin tailed weaner lambs (7-11.80 kg) was at random assigned to either treatments I (T1) or II (T2). T1 was restrictively fed for five weeks whereas T2 were fully fed during the experiment.Â At the end of a 5-week restriction period, T1 lost live weight of 11.45% whereas T2 gained weight of 11.95%.Â Glucose utilization rate was estimated by injecting a bolus of glucose into one jugular vein with a dose of 0.30 g per kg live weight.Â Blood samples (2.50 ml) were taken from the other jugular vein 5 min before injection and 10, 20, 30, 40, 50, 60 after injection of a bolus of glucose.Â Collected data was analyzed using unpairedÂ âtâ test with equal replicates. Statistical analysis indicated that the rate of whole body glucose utilization of T1 (meanÂ±SE) was significantly (P<0.01) slower than that for T2 (0.88 Â± 0.06 vs. 1.79 Â± 0.25%/minute).Â Mean basal blood glucose concentration of T1 and T2 (meanÂ±SE) were 3.16 Â± 0.21 and 4.19 Â± 0.04 mM, respectively.Â In conclusion, feed restriction for a long period of time impaired whole body glucose utilization. (Animal Production 8(1): 44-49 (2006)Â Key Words : Sheep, glucose, concentration, blood